2016
DOI: 10.1016/j.msea.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Deformation microstructures and tensile properties of an austenitic stainless steel subjected to multiple warm rolling

Abstract: The deformation microstructures of a 316L-type austenitic stainless steel subjected to multiple bar rolling to a total strain of 2 at temperatures of 773-1173 K and their effect on the mechanical properties at ambient and elevated temperatures were studied. The multiple warm rolling was accompanied by significant grain refinement. The finally evolved transverse grain size decreased from 3.4 mm to 0.85 mm with a decrease in the rolling temperature from 1173 K to 773 K. The warm rolled steel samples were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 31 publications
9
17
0
Order By: Relevance
“…[24,25] In this case, the mean grain size can be also expressed by a power law function of Z with a much smaller exponent of about À 0.1. [45,46] The present data (the range of warm working in Figure 10) display remarkable deviation from the D DRX~Z À0.1 line as could be expected for CDRX. This discrepancy is caused by insufficient strain for the development of continuous dynamic recrystallization, which requires much larger strain to make a meaningful contribution to the microstructure evolution.…”
Section: A Mechanisms Of Microstructure Evolutionsupporting
confidence: 70%
See 1 more Smart Citation
“…[24,25] In this case, the mean grain size can be also expressed by a power law function of Z with a much smaller exponent of about À 0.1. [45,46] The present data (the range of warm working in Figure 10) display remarkable deviation from the D DRX~Z À0.1 line as could be expected for CDRX. This discrepancy is caused by insufficient strain for the development of continuous dynamic recrystallization, which requires much larger strain to make a meaningful contribution to the microstructure evolution.…”
Section: A Mechanisms Of Microstructure Evolutionsupporting
confidence: 70%
“…À 0.33, which is an average of those of À 0.27 to À 0.4 reported in other studies on discontinuous dynamic recrystallization (DDRX) in austenite during hot working. [44][45][46][47] On the other hand, the deformation microstructures evolved during warm deformation are generally associated with continuous dynamic recrystallization (CDRX). [24,25] In this case, the mean grain size can be also expressed by a power law function of Z with a much smaller exponent of about À 0.1.…”
Section: A Mechanisms Of Microstructure Evolutionmentioning
confidence: 99%
“…Given the typical grain sizes in similar alloys subjected to similar processing [69,70], it is expected that the grain size of the current samples will be such that the grain size strengthening will follow the Hall-Petch relationship (Equation (6), where σ y is the yield strength, σ 0 is the yield strength attributed to other strengthening mechanisms, i.e., the yield strength of the material in the very large-grained condition, equal to σ P + σ S + σ O in the current study, K g is the Petch coefficient, and d is the grain size and is expected to be between 1 µm and 100 µm) [37][38][39][40][41].…”
Section: Work Hardening and Grain Refinementmentioning
confidence: 99%
“…Approximate values may be calculated from thermokinetic precipitation simulations in Thermo-Calc Prisma (Figure 4). Another approach asserts that the Orowan strengthening can be calculated by using the Bacon-Kocks-Scattergood equation (Equation (11), where A ≈ 0.2 is a coefficient related to the type of dislocations [67][68][69][70][71][72][73], D is a harmonic average that describes the two limit cases of the Orowan strengthening (small, widely spaced particles and relatively large, closely spaced particles), and all other symbols have the meaning defined previously). The harmonic average is given by Equation (12), where D p = 2r p , and L P = L + 2r p is the separation of the precipitate centers [81].…”
Section: Precipitate Strengtheningmentioning
confidence: 99%
“…More generally, since austenite and ferrite phases have different elastic and plastic properties in addition to different thermal expansion coefficients, they should act differently during a deformation process. The microstructural and associated hardening evolutions that take place during the hot deformation of single phase austenitic and ferritic stainless steels have been extensively investigated in several research works [7][8][9][10][11][12]. It was already concluded that easy dislocation annihilation and rearrangement, leading to dynamic recovery, occurs in ferrite.…”
Section: Introductionmentioning
confidence: 99%